OPTIMAL CONDITIONS FOR QUALITY DEVELOPMENT OF DRIED SEA BASS: CASE STUDY OF BANG KLUEA COMMUNITY, BANG PAKONG DISTRICT, CHACHOENGSAO PROVINCE - Kakham, Phumiphat; Mongkhon, Chatchawarn; Pinthong, Jakaphan; Prateepchanachai, Sarinya (Srinakharinwirot University Journal of Sciences and Technology, 2022)
Sea bass are economically important for Bang Pakong district, Chachoengsao province causing farmers to be a career to raise a lot of sea bass but currently experiencing a problem of oversupply. This research aims to develop the sea bass products by using hot air oven dryer. The study of the drying conditions, such as sample preparation, thickness and drying temperature on drying kinetics. Study of product quality in color, water activity, hardness, toughness, percentage of shrinkage and analysis of function groups of dried sea bass products by using Fourier Transform Infrared Spectroscopy technique that affects physical characteristics. The samples were prepared by immersing in 1%(w/v) citric acid solution combined with 3%(w/v) NaCl and without any processing as a control sample. The study result was found that sea bass fillets at a thickness of 5 mm, the drying temperature of 80oC, was immersed in 1%(w/v) citric acid solution combined with 3%(w/v) NaCl led to drying time was shorter than control sample. The color quality was showed that the lightness (L*) increased, the redness (a*) and the yellowness (b*) decreased. The water activity was 0.61, the hardness was less than the control sample but there was no significant difference and the percentage of shrinkage was less than control sample. Analysis of function groups of dried sea bass found that the peak position significantly at 2,925, 2,854, 1,743 and 1,170 cm-1 decreased, indicating that the preparation of sea bass fish products before drying can reduce lipid oxidation led to make delay the occurrence of unusual odors and flavors and also it is cause of the hardness of the product is less than the control sample. In addition, it was found that small peaks appeared between 1,300-1,200 cm-1 and 850 cm-1 increased which relates to products that are slightly salty. Therefore, this dried sea bass products is suitable for use as a guideline for product development for farmers in the future.